2021
DOI: 10.1007/s10965-021-02419-y
|View full text |Cite
|
Sign up to set email alerts
|

Ring opening polymerization of ε-caprolactone initiated by titanium and vanadium complexes of ONO-type schiff base ligand

Abstract: A phenoxy-imine proligand with the additional OH donor group, 4,6-tBu2-2-(2-CH2(OH)-C6H4N = CH)C6H3OH (LH2), was synthesized and used to prepare group 4 and 5 complexes by reacting with Ti(OiPr)4 (LTi) and VO(OiPr)3 (LV). All new compounds were characterized by the FTIR, 1H and 13C NMR spectroscopy and LTi by the single-crystal X-ray diffraction analysis. The complexes were used as catalysts in the ring opening polymerization of ε-caprolactone. The influence of monomer/transition metal molar ratio, reaction ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In addition to a recent report from Plaman and Durr regarding the catalytic application of phenoxyimino Nb and Ta ethoxides, and Al-Khafaji and co-worker’s work encompassing the use of calixarene-supported NbCl 5 as a ROP initiator, reports from the groups of Chakraborty and Redshaw concerning, respectively, the use of Nb and Ta imino phenoxides and tetraphenolate-supported Nb and Ta species, , and a poorly controlled trihydridoniobocene system reported by Otero and co-workers, remain the only examples of these metals being successfully applied to the polymerization of ε-caprolactone. Several vanadium-catalyzed protocols have also been reported for the ROP of cyclic esters, including for ε-caprolactone. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to a recent report from Plaman and Durr regarding the catalytic application of phenoxyimino Nb and Ta ethoxides, and Al-Khafaji and co-worker’s work encompassing the use of calixarene-supported NbCl 5 as a ROP initiator, reports from the groups of Chakraborty and Redshaw concerning, respectively, the use of Nb and Ta imino phenoxides and tetraphenolate-supported Nb and Ta species, , and a poorly controlled trihydridoniobocene system reported by Otero and co-workers, remain the only examples of these metals being successfully applied to the polymerization of ε-caprolactone. Several vanadium-catalyzed protocols have also been reported for the ROP of cyclic esters, including for ε-caprolactone. …”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and characterization of the phenoxy-imine proligand, L 1 H 2 , as well as the corresponding titanium ( Ti-L 1 ) and vanadium ( V-L 1 ) complexes, were reported in our previous communication [ 41 ]. In this work, we synthesized two novel [ONO]-type proligands and corresponding complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Despite numerous reports that describe the behavior of titanium complexes in the ROP, there have been published only very few papers on vanadium complexes bearing ligands with O and N donor atoms, e.g., bi- and tridentate phenoxy-imine, tetradentate [ONNO]-type, and ligands derived from potentially tridentate 6-bis(o-hydroxyaryl)pyridines [ 41 , 42 , 43 ]. All of them were shown to promote the polymerization of ε -caprolactone but they turned out to be significantly less effective than titanium complexes with multidentate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we and others have found that very high catalytic activities and thermally robust systems are accessible for α-olefin polymerization when conducted in the presence of co-catalysts such as dimethylaluminium chloride and the re-activator ethyl trichloroacetate [19][20][21][22][23][24][25][26][27][28][29][30][31], as well as ethylene copolymerization with the likes of propylene, 1-hexene or norbonene [32][33][34][35][36][37][38][39][40][41]. Moreover, a number of vanadyl-containing systems have shown promise in the ROP of cyclic esters [42,43], whilst other systems have been shown to be promising for both ROP and α-olefin polymerization [44][45][46][47][48][49]. We also note the favourable toxicity of vanadyl complexes; for example, vanadyl sulfate is not only used as a supplement but has shown promising behaviour against Type 2 diabetes [50].…”
Section: Introductionmentioning
confidence: 98%